Influencia del clima laboral en la productividad de la Mipyme “Carluis restauracion y modificacion automotriz”. - Espinoza Bajaña, Zuleyka Yanara (2025)
The objective of this investigation is to evaluate the impact of the work environment on the productivity of the SME "Carluis Restauración y Modificación Automotriz," which is situated in the city of Quevedo, Ecuador. The work environment, which is defined as the subjective perception of employees regarding their workplace, is a critical factor in employee productivity, well-being, and motivation. Surveys, semi-structured interviews, and direct observation were implemented to collect data regarding the primary variables that influence the work environment within the organization, including leadership, communication, motivation, physical workshop conditions, and interpersonal relationships. This mixed approach integrates quantitative and qualitative methodologies. The findings suggest that, despite the company's commitment to fostering a positive work environment that is founded on principles of respect and collaboration, there are critical areas that necessitate intervention. The well-being and performance of employees are adversely affected by the insecurity conditions in the area, insufficient incentives, space limitations, and the absence of structured training. The conclusions indicate that the company's productivity and competitiveness would be substantially enhanced by enhancing these aspects. It is advisable to enhance the physical conditions of the workshop, implement continuous training strategies, and provide sufficient incentives. This research also offers a theoretical and practical framework that can be implemented by other small and medium- sized enterprises (SMEs) in the automotive industry, thereby enhancing their productivity and organizational structure